A Analysis of Preventive Maintenance Schedule of Xym1900 Vertical Roller Mill Crusher Machine using MTBF (Mean Time Between Failures) Method Based on RCA (Root Cause Analysis) - Muhammad Alfin; Rusindiyanto Rusindiyanto (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2025)
The reliability and performance of heavy machinery are critical to maintaining consistent production in the cement industry. This study analyzes the preventive maintenance schedule of the XYM1900 Vertical Roller Mill crusher machine at PT XYZ, where frequent breakdowns have contributed to production inefficiencies and increased operational costs. The research employs the Mean Time Between Failures (MTBF) method to evaluate the reliability of key machine components and identify optimal maintenance intervals. Additionally, Root Cause Analysis (RCA) is used to trace the underlying causes of recurring failures. Maintenance and failure data were collected over a one-year period to calculate MTBF values for critical components, including the grinding roller, hydraulic system, and gearbox. RCA findings indicate that improper lubrication, delayed part replacements, and environmental factors such as dust contamination are the primary contributors to equipment failure. Based on the analysis, revised maintenance schedules were proposed to reduce unplanned downtime and extend component life. The results demonstrate that implementing a data-driven preventive maintenance plan can significantly enhance equipment reliability and support operational efficiency.